What is an “Explanation” of Behavior? - Simon, Herbert A. (Psychological Science, 1992)
The cognitive “revolution” in psychology introduced a new concept of explanation and somewhat novel methods of gathering and interpreting evidence. These innovations assume that it is essential to explain complex phenomena at several levels, symbolic as well as physiological; complementary, not competitive. As with the other sciences, such complementarity makes possible a comprehensive and unified experimental psychology. Contemporary cognitive psychology also introduced complementarity of another kind, drawing upon, and drawing together, both the behaviorist and the Gestalt traditions.